Partisipasi Petani dalam Kegiatan Penyuluhan dan Pelatihan Teknis Budidaya Jamur Merang di Desa Kutaampel, Kecamatan Batujaya, Karawang - Mariyani, Siti (Jurnal Budiman: Pembangunan dan Pengabdian Masyarakat Nusantara, 2023)
Mushrooms are an alternative in meeting the need for high protein foods, but their availability is not matched by increased production. Efforts that can be made to increase the productivity of straw mushroom is to provide counseling and training to farmers about mushroom cultivation. Counseling and training on straw mushroom nurseries was given to farmers in Kutaampel Village. This paper aims to determine the participation of farmers in Kutaampel Village in counseling activities and technical training on cultivation and making seed baglogs for spreading F3 and F4 edible mushroom UNSIKA. The method used is the andragogy training method and will be held on 06 October 2022 in Kutaampel Village. The data analysis used is descriptive with reference to Arnstein’s (1969) theory, namely the theory of participation which is called The Ladder of Participation theory. Based on the data analysis conducted, the level of participation of farmers in Kutaampel Village in participating in extension activities and technical training on cultivation and making baglogs for spreading F3 and F4 Unsika mushroom seeds was seen from the forms of farmer participation, namely presence, knowledge and benefits. The level of farmer participation in Kutaampel Village is at the level of the fourth rung of the consultation ladder out of a total of eight rungs of the Arnstein participation ladder (manipulation, Therapy, Informing, Consultation, Placement, Partnership, Delegated power, and Citizen control). Key Words: Cultivation, Participatio, Straw Mushroom